Engineering field tests for alkali‐aggregate reaction. (16th February 2017) - Helene, Paulo; Carvalho, Mariana; Pacheco, Jéssika
Abstract : The Paulo Guerra Bridge in Recife, Brazil, was constructed in 1977. After about 15 years some pathological symptoms appeared, such as map cracking, concrete expansion, steel corrosion, and leaching stains. This paper presents a discussion of the specific inspections conducted, which included visual observation of the foundation blocks (pile caps), core extraction, ultrasonic pulse velocity tests, carbonation tests, measurements of chloride concentration, electrochemical resistivity, corrosion potential, compressive strength, and modulus of elasticity as well as X‐ray diffraction and microscopy evaluations. The results of the inspection showed the occurrence of generalized alkali‐aggregate reactions (AARs) on the pile caps (foundation blocks) of the bridge. The recommended repair for the pile caps was confinement to resist tensile stresses of 4 MPa.